OP2 18F-fluoride PET/MR in cardiac amyloid: a comparison study with aortic stenosis and age and sex matched controls. (7th September 2020) - Andrews, Jack PM; Trivieri, Maria Giovanni; Everett, Russell; Spath, Nicholas; MacNaught, Gillian; Moss, Alastair J; Doris, Mhairi K; Pawade, Tania; van Beek, Edwin JR; Lucatelli, Christophe; Newby, David E; Robson, Philip; et al.
Abstract : Introduction: Cardiac MR is widely used to diagnose cardiac amyloid but cannot differentiate AL and ATTR subtypes: an important distinction given their differing treatments and prognoses. We used PET/MR imaging to quantify myocardial uptake of 18F-fluoride in ATTR and AL amyloid patients as well as participants with aortic stenosis and age/sex matched controls (both negative controls). Methods: In this prospective multi-centre study, patients were recruited in Edinburgh and New York and underwent 18F-fluoride PET/MR imaging. Standardised volumes of interest were drawn in the septum and areas of late gadolinium enhancement to derive myocardial standardised uptake values (SUV) and tissue to background ratio (TBRMEAN ) after correction for blood pool activity in the right atrium. Results: 53 patients were scanned. 18 with cardiac amyloid (10 ATTR and 8 AL), 13 controls and 22 with aortic stenosis. No differences in myocardial TBR values were observed between participants scanned in Edinburgh and New York. Mean myocardial TBRMEAN values in ATTR amyloid (1.13±0.16) were significantly higher than controls (0.84±0.11, p=0.0006), aortic stenosis (0.73±0.12, p<0.0001) and those with AL amyloid (0.96±0.08, p=0.01). TBRMEAN values within areas of late gadolinium enhancement provided clear discrimination between patients with ATTR (1.36±0.23) and all other groups (e.g. AL [1.06±0.07, p=0.003]). Indeed, a TBRMEAN threshold >1.14 in areas of LGE demonstrated 100% sensitivity (C.I. 72.25 – 100%) and 100% specificity (C.I. 67.56 – 100%) for ATTR compared to AL amyloid (AUC 1, p=0.0004). Conclusion: Quantitative 18F-fluoride PET/MR imaging can distinguish ATTR amyloid from other similar phenotypes and holds major promise in improving the diagnosis of this condition and helping to tailor appropriate treatments to those most likely to benefit.